Asia Pacific Graduate Education Comparative Policies and Regional Developments - Neubauer, Deane E.; Buasuwan, Prompilai; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2016)
This volume examines the changes taking place within graduate education in the Asia Pacific Region. A collection of essays by distinguished scholars from eight Asia Pacific nations links profound changes occurring in the economies and societies of the region to the many changes taking place within higher education. Focusing on how the dynamics of a changing global economy are affecting the ways higher education institutions are responding, particular changes are seen to be taking place in graduate education as many societies experience the need to produce graduates of high quality with elevated qualifications. Such changes are not without challenge or difficulty as issues of finance. Questions of appropriate directions of innovation and overall higher education capacity continue to frame the broader issue of the changing nature of graduate education. .
PART I: CHANGING DYNAMICS OF ASIA PACIFIC GRADUATE EDUCATION -- 1. Novel Forms of Financing Cross-Border Graduate Education; Chris Ziguras.-2. Graduate Education in Asia Pacific Higher Education: Changing Roles and Purposes; Edilberto C. de Jesus -- 3. Graduate Degrees in the Emergent Political Economy of Contemporary Globalization; Deane Neubauer -- PART II: GRADUATE EDUCATION IN COMPARATIVE COUNTRY SETTINGS.-4. An Examination of Employment Outcomes for Graduate Education at the University of Hawaii; Pearl Imada Iboshi, Ming Zhang, Sanford Beppu, and Winnie Wu -- 5. The Postgraduate Research Student Experience in Malaysia; Koo Yew Lie and Vincent Pang.-6. Learning Outcomes Assessment in Graduate Education: A Comparative Overview between United States and ASEAN; Stewart Sutin and Somkiat Kamolpun.-7. Challenges and Strategic Development of PhD Education of Fu Jen Catholic University; Shang-Shing P. Chou, Chih-Hsien Yang, and Gregory S. Ching.-8. Improving the Quality of Contemporary Graduate Education: a Proposal for Nurturing Future Civic-Minded Professionals; Farrah Dina Yusop.-9. Industry-Oriented Graduate Programs in Thailand: A Review; Bundit Fungtammasan.-10. (3z(BDiploma Disease(3y (Bin Thai Higher Education; Prompilai Buasuwan and Michael Jones.-11. Exploring Researcher Motivation: Implications for PhD Education; Robyn Barnacle, Denise Cuthbert, and Richard Laurie -- 12. Conclusion; Deane Neubauer and Prompilai Buasuwan. .s
Keywords: Education; Educational policy; ducation and state; Education; Educational Policy and Politics; Electronic books